Política externa brasileira para o meio ambiente e o desenvolvimento sustentável: o posicionamento brasileiro durante as conferências ambientais da ONU - Figueiredo, Julia Soares (Universidade Federal do Tocantins, 2019)
Brazil has already played a leading role in the international environmental regime. Since the emergence of the environment as an important and definitive agenda in the global political agenda, Brazil participated, proposed and sometimes led the international negotiations on the theme. A few years ago, however, environmental policy was clearly subordinated to the dominant economic interests in national politics, as evidenced by the construction of the Belo Monte plant, major infrastructure works, indigenous politics, legislation, taxation, and various mining activities, and many other cases. Within this context, the Brazilian external and internal positioning for the environment is studied based on the UN international environmental conventions, in the period of 1972 to 2012. The objective of this work is to indicate if the concept of sustainable development is applied in domestic politics with the same intensity in which it is defended in its foreign policy for the environment. Through the research it is possible to conclude that there are different positions in domestic and external environmental policies. To answer the research question a bibliographic review of the topics of sustainable development and foreign policy analysis is done, in addition to presenting a case study of the construction of the Belo Monte Power Plant.